The Influence of Psychological Capital and Person Organization Fit on Teacher Performance with Organizational Commitment as Mediation - Agus Budi Santosa; Agung Nusantara; Sri Nawatmi; Febri Sebastian (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2022)
The teacher is a key element in the education system, especially in schools because of the teacher's role in transforming knowledge in education. Therefore, schools can improve teacher performance in order to achieve predetermined educational goals. This article will analyze the influence of psychological capital and person organization fit on teacher performance by mediating organizational commitment. This research uses quantitative analysis. The population in this study were 108 teachers of Junior High School in Bantarbolang District. Analysis of data techniques used regression analysis. The results of the research on model 1 show that psychological capital and person organization fit have a positive effect on organizational. In model 2, psychological capital and organizational commitment have a positive effect on teacher performance while organizational people do not. The results of the mediation test show that organizational influence does not mediate the effect of psychological capital on teacher performance, but organizational commitment mediates.